PEMASARAN JASA PENDIDIKAN DI ERA SOCIETY 5.0 - Rahman, Tatang Aulia (TADBIR : Journal of Islamic Education Management, 2024)
Marketing educational services in the Society 5.0 era is an interesting and relevant topic in an increasingly digital era. Society 5.0 refers to the concept of a society that is closely connected to technology, where innovation and digitalization are the center of attention. In the educational context, marketing of educational services must also follow these developments by utilizing technology and appropriate marketing strategies. This article will discuss further about marketing educational services in the Society 5.0 era and how important it is to adopt appropriate marketing strategies for the future of education. Marketing educational services has become a very important aspect in facing the Society 5.0 era. Why is that? Because in a society that is increasingly connected to technology, the needs and preferences of prospective students have also changed. They are more likely to seek information and make decisions via the internet and social media. Therefore, to remain relevant and competitive in the education industry, it is very important for education service providers to adapt to the trends and changes occurring in this era